Molecular Cloning And Characterization Of Cdna Encoding For Enzymes In The Carotenoid Biosynthetic Pathway Of Oil Palm (Elaeis Guineensis Jacq.) - Abd Rasid, Omar (2008)
The potential health benefits of carotenoids, in particular as anticancer and antioxidant agents, have recently been highlighted. Extensive studies have been conducted to elucidate the plant carotenoid pathway. Oil palm is known to be the richest natural source of carotene. However, to date, there has been no work carried out to elucidate the pathway in this species. The lack of the knowledge could restrain the potential advantages of the plant for further improvement through genetic modifications. This work is the first effort towards the understanding of the oil palm carotenoid biosynthesis pathway. The aim was to isolate cDNA clones encoding the oil palm lycopene β-cyclase (LCYb), lycopene ε-cyclase (LCYe), phytoene dusaturase (PDS) and zeaxanthin epoxidase (ZEP). The first two enzymes have been suggested to have a regulatory control over the formation of carotene. Thus, their genes are believed to have an important and urgent biotechnological application. Fragments containing partial sequences of these genes were successfully generated through reverse transcriptase polymerase chain reaction (RTPCR) using degenerate primers. The complete DNA sequence of these fragments were determined. Primers were then designed based on these sequences to facilitate the amplification of the 3’ and 5’ end regions of the transcripts. Both ends were successfully obtained for both cyclases. A consensus sequence of 1962 bp and 1759 bp was generated for oil palm lcye and lcyb, respectively. An open reading frame (ORF) of 1617 bp encoding 539 amino acid (AA) residues was identified for lcye. Similarly, an ORF of 1509 bp encoding for 503 AA residues was also identified for lcyb. Deduced AA sequences were shown to be highly identical to their respective counterparts from other plants at about 80% identity. Although the enzymes were functionally equivalent, they were shown to share little resemblance at about 30% identity. However, oil palm LCYb was shown to share a relatively high identity to plant neoxanthin and capxanthin-capsorubin synthases, suggesting the common ancestor of the cyclases and synthases. RTPCR amplifications using degenerate primers were also successfully used to generate fragments of 865 bp and 567 bp for oil palm pds and zep, respectively. Subsequently, the deduced AA sequence for both fragments was identified based on comparison to peptide sequences of their counterparts from other plants. Both oil palm PDS and ZEP were shown to be highly identical to their respective counterparts from other plants at about 85%. The regulation of these four carotenogenic genes as well as phytoene synthase was studied in developing mesocarp tissues using real-time PCR analysis. The results indicated that all of the carotenogenic genes were expressed at a low level in the tissues tested. psy and pds were shown to be expressed at a relatively higher level in young and late developing mesocarp tissues, as well as in leaves. A similar expression level was observed for the cyclases, although at a relatively lower level than the psy and pds level. Nevertheless, the expression of these genes seemed to be correlated and thus believed to be regulated for the accumulation of carotenoids in the tissues both for developmental process and storage. The copy number of the two oil palm cyclase genes was examined using Southern analysis. The results indicated that there was at least one of the restriction enzymes used gave a single hybridized band. This finding strongly suggested that the two cyclase genes are present in a single copy in oil palm. In conclusion, the full length cDNAs coding for lycopene β-cyclase and lycopene ε-cyclase and partial cDNAs for phytoene desaturase and zeaxanthin epoxidase were successfully obtained and characterized. This work provides the required genetic material for the modification of oil palm carotenoid content, especially for the production of high lycopene transgenic oil palm. Furthermore, the results of the expression study provide very valuable information for formulating an effective strategy for oil palm carotenoid genetic engineering especially toward the increase of lycopene by down-regulating the two cyclase genes.